Molecular Docking Study of Isoflavonoid Erythrina variegata To Plasminogen Receptor as Thrombolytic Agent on Myocardial Infarction Disease - Rizky Arcinthya Rachmania; Hariyanti; Dewi Susilawati (Jurnal Jamu Indonesia, 2022)
Erythrina variegata is one of the plants that have efficacy as thrombolytic agent. Isoflavonoid compound has the potential to accelerate the changes of plasminogen which plays important role in the forming of fibrin, that causes the formation of fibrin clots that can clog the arteries thus causing myocardial infarction. This study aimed to look at the activity of isoflavonoid compounds from Erythrina variegata bark which are expected to be candidates for thrombolytic drugs. This research aims at looking for the interaction of isoflavonoid compounds of bark  which is expected can be thrombolytic drug candidates. The method used in this research was the molecular docking with Autodock Vina and PyMOL software. The results showed that the value of ΔG binding affinity as ligands standard streptokinase -8.4 kcal/mol and isoflavonoid derivatives that have ΔG binding affinity value was lowest for the folitenol -11.5 kcal / mol and orientanol C -11.4 kcal/mol. Can be concluded that isoflavonoid derivatives in Erythrina variegata have better binding potential compared to streptokinase as standard ligands.